MicroRNAs are novel non-invasive diagnostic biomarkers for pulmonary embolism: a meta-analysis - Deng, Han-Yu; Li, Gang; Luo, Jun; Wang, Zhi-Qiang; Yang, Xiao-Yan; Lin, Yi-Dan; Liu, Lun-Xu (Journal of Thoracic Disease, 2016)
Backgrounds: The diagnosis of pulmonary embolism (PE) still remains difficult in clinical practice. MicroRNAs (miRNAs) have been widely investigated as biomarkers for various diseases. However, the diagnostic biomarker value of miRNAs in the diagnosis of PE is unclear. Therefore, we conducted this meta-analysis to establish the diagnostic power of miRNAs for PE diagnosis. Methods: A systematic literature search in PubMed and Embase was conducted to identify relevant studies dated up to July 22, 2016. Data on sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were pooled from those included studies. Summary receiver operating characteristic (SROC) curves were used to summarize overall diagnostic power of miRNAs for PE diagnosis. Results: A total of three studies with five types of miRNAs covering 254 participants were included in our meta-analysis. The overall pooled results for sensitivity, specificity, PLR, NLR, and DOR of miRNAs for PE diagnosis were 0.83 [95% confidence intervals (CI): 0.67–0.92], 0.85 (95% CI: 0.72–0.92), 5.4 (95% CI: 2.7–10.9), 0.20 (95% CI: 0.10–0.44), and 26.00 (95% CI: 7.00–101.00), respectively. The area under the SROC curve was 0.90 (95% CI: 0.87–0.92). Even though heterogeneity was observed in the analysis of sensitivity, there was no evidence of publication bias. Conclusions: MiRNAs could serve as novel non-invasive diagnostic biomarkers of PE with a relatively high diagnostic power. More researches, however, are needed to explore the diagnostic as well as therapeutic values of miRNAs for PE.